Synovial Macrophages in Rheumatoid Arthritis: The Past, Present, and Future - Jiajie Tu; Xinming Wang; Xun Gong; Wenming Hong; Dafei Han; Yilong Fang; Yawei Guo; Wei Wei (Mediators of Inflammation)
The ontogeny of macrophages in most organs has already been established. Owing to the limited number and inaccessibility of synovial macrophages (SMs), the origin of SMs has not been fully elucidated. Previous studies suggested that SMs have two major origins, namely, tissue-resident and monocyte-derived SMs. However, no systematic analysis to identify SM ontology in either physiological or pathological conditions has been available to date. In this review, we summarize relevant studies on the two main origins of SMs in rheumatoid arthritis (RA) and forecast the future research directions for this field. Furthermore, we discuss the current state of RA therapy that is based on targeting different SM subsets.